Two Different Worlds: Television as a Producer’s Medium - Coleman, Robin R. Means; Cavalcante, Andre M. (Watching While Black, 2012)
Although discourses regarding 1980s representations of Blackness on television heavily focus on The Cosby Show, its NBC spin-off series, A Different World, depicting student life at a historically Black college, was equally groundbreaking and deserving of critical attention. Looking to transfer the appeal and audience share of The Cosby Show to A Different World, the spin-off show’s first season centered on the life of The Cosby Show’s star Denise Huxtable (Lisa Bonet) at Hillman College. A Different World’s story provides an illuminating case study of the role and power of television producers, highlighting their influence over a show’s narrative and
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; États-Unis (corpus analysé)

Introduction: I See Black People - Smith-Shomade, Beretta E. (Watching While Black, 2012)
This project has been engaging my thoughts for nearly a decade. I was forced to actually address it while sitting in our temporary home in Ile-Ife, Nigeria, watching world satellite TV with virtually no Blacks on it. In Nigeria, I became acquainted with Paris-based Fashion TV, U.S.-based Style Network, and the Australian production McLeod’s Daughters. Outside of M-Net’s Africa Magic, a network dedicated to showing Nollywood productions primarily, television was anything but Black. This whitening of the televisual frame, even in Black Africa, made me begin to consider the dearth of knowledge circulating about Black television programming, even when abundance
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Debating Women’s Issues on Turkish Television: Exploring the Role of Political Power in Women’s Talk - Özcan, Esra (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In this contribution, I provide an in-depth rhetorical and textual analysis of a television debate program broadcast in 2015 on the mainstream television news channel, Habertürk TV in Turkey. The debate brought together women committed to varying political projects, including Kemalism, Islamism, leftist movements, Kurdish women’s movements, and feminism. I find this debate program unique because it took place at a crucial moment in Turkey’s recent history, preceding increasing restrictions on the media that eventually cost more than half of the program participants’ jobs and positions. In my analysis, I focus on how the program’s moderator and the women participants define “women’s issues” in an increasingly authoritarian and conflictual political climate where women are divided with regard to supporting or opposing the Justice and Development Party’s (Adalet ve Kalkınma Partisi—AKP) political program. The results of my analysis show that “sisterhood” does not provide common ground for women in a politically polarized environment and women with more political power dominate the conservation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Refashioning Chinese Television Through Digital Fun - Bai, Ruoyun (The Routledge Companion to Global Television, 2019)
This chapter discusses how Chinese television has been refashioned by the digital entertainment industry, and contends that new genres, identities, and representations have emerged in recognition of youths as the most valuable and desirable category of audience. It does so by way of three case studies. The first illustrates the symbiotic relationship between online literature and television drama production, and how the former contributes to the fantastical turn of Chinese television. The second seeks to understand the emergence of new cultural figures of “supreme heroine” and “sweet males” in the context of the rise of female fandom in contemporary Chinese popular culture. The third reveals how traditional television content, or in this case a political drama, may be recreated by online distributors and influencers so as to be aligned with the habits, attitudes, and preferences of the younger audiences. The chapter concludes that to understand contemporary Chinese television culture, the Internet and social media must become an integral component of inquiry because of their powerful remediating role in the public communication of any cultural text.
Num Pages: 12
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Identités diasporiques; Canada (lieu de production du savoir); Chine (corpus analysé); _Nettoyé

Neoliberal Multiculturalism, Outsourced - Nadkarni, Asha (The Routledge Companion to Global Television, 2019)
This essay examines the 2010 NBC situation comedy Outsourced, with special attention to its representation of the racial politics surrounding business process outsourcing to India. Specifically, it discusses how Outsourced participates in what Jodi Melamed calls “neoliberal multiculturalism” to work through, symbolically and narratively, the realities and contradictions of globalized economies as they are experienced. By staging the dilemmas of outsourcing through the specter of the white male middle manager traveling to India to train Indian call center workers, Outsourced minimizes the affective labor necessarily performed by Indian call center workers and dramatizes outsourcing as a crisis of white U.S. masculinity alone. Moreover, it figures our white male protagonist as the global multicultural citizen to be emulated insofar as he models the appropriate attitude toward outsourcing and toward “other” cultures in general. Finally it suggests that the failure of the show has less to do with issues of cultural stereotyping and more to do with the failure of neoliberal multiculturalism to soothe anxieties around changing global economies.
Num Pages: 10
Keywords: 1-TV; 2-Approches sociologiques; 2-Méthodologie de recherche décoloniale; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Petit guide sur le cinéma des femmes - Ouellet-Cummings, Catherine (Ciné-Bulles, 2011)
Thérèse Lamartine est bien connue des milieux féministes. Détentrice d’une maîtrise en études cinématographiques, elle a publié Elles, cinéastes... ad lib, en 1985, aux Éditions Remue-ménage, dans lequel elle présentait des réalisatrices de diverses origines, actives entre 1895 et 1981. En 2009, elle publiait Soudoyer Dieu, un roman scrutant la longue et inconsolable douleur d’un groupe de femmes après la tuerie de Polytechnique. Avec Le Féminin au cinéma, une petite plaquette consacrée aux films «de femmes» ou, comme elle le précise, aux films qui «sculptent un art du mieux-vivre la mixité dans nos sociétés ou [qui] débrident les stéréotypes et nous dérident à la fois», Lamartine ouvre les portes d’un monde cinématographique souvent méconnu et rend hommage à des femmes de cinéma, autant derrière que devant la caméra. En sortant ces femmes de l’ombre, elle met au jour un cinéma riche et original, mais méconnu.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créatrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Re-Inventing Art Practices: Indigenous Women Artists Building Community through Art and Activism in Rural and Remote Manitoba - Nagam, Julie (University of Manitoba, 2006)
his thesis documents and explores community-based and socially engaged art by Indigenous women artists. Their artwork is impacting and strengthening communities in Manitoba. The Thesis explores the use of dialogical aesthetics in performance and socially-engaged art by Indigenous women artists in rural and remote areas of Manitoba, and relates these aesthetics to the concept of activism through their art and relationship to their community. The aim of this research and this paper is to document, support and expose the work of a small pocket of Indigenous women artists in Manitoba who are acting as activists or social change agents based on their artwork. I have arrived at this conclusion first by their personal testimonies, second, by their art being socially conscious and lastly, by their art practices entrenched in the framework of dialogical aesthetics, community-based and site-specific ideologies.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé